Perspectives and facilities in development of viticulture in Serbia - Mihajlović, Božidar; Sivčev, Branislava; Petrović, Daliborka; Ranković-Vasić, Zorica (Economics of Agriculture, 2010)
This "Bahus beverage" represents the most marketed product among all those which are preferred to be labeled as ecologic. Therefore, Zenobije, the Athenian, (sixth century before Christ), the best expert of wine soul, made a famous statement – En oino eleteia- which was later translated by the Romans into- In vino veritas- which we then literally embedded it in our everyday life-Truth is in the wine. So, the wine has no definition. All those experiences, which had been gathered during many millenniums and passed from generation to generation through myths and legends, enable the human beings to enjoy in many different pleasures. They also raise the wine to the level of divine drink, assigning even new meanings to it- victory of life and prudence of senses. So, considering the geographical and climatic position of the country, Serbia has all necessary conditions for solid growing table and wine varieties and wine production. Precisely because of these conditions, thise products get their medical recognition, which means that for example wine, as cultural taste of modern human being, can be in function of preserving and preventing the humane health. And this is the main factor, which can bring million foreign in come to the country and employ 250 to 300 thousand people. It is even desirable to create small and medium enterprises, or business inside the family household with all preconditions, which this kind of activity demands.